Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
- y = 8
- x = 16
Explanation:
- x + y = 24
- x = 2(y)
solve, insert equation 2 into 1
- 2(y) + y = 24
- 3(y) = 24
- y = 8
Find x:
x = 2(y)
x = 2(8)
x = 16
Answer:
y = 8
x = 16
Step-by-step explanation:
Given equations:
- x + y = 24
- x = 2y
Reorganize the equations:
[tex]\left \{ {{x + y = 24} \atop {x = 2y}} \right.[/tex]
[tex]\left \{ {{x + y = 24} \atop {x - 2y = 0}} \right.[/tex]
Subtract:
[tex]\left \{ {{x + y = 24} \atop {x - 2y = 0}} \right.[/tex]
[tex]{ {{[x - x] + [y - (-2y)]= 24 - 0}[/tex]
[tex]{ {{x - x + y + 2y= 24}[/tex]
[tex]3y= 24}[/tex]
Divide 3 both sides:
[tex]\dfrac{3y}{3} = \dfrac{24}{3} }[/tex]
[tex]y = 8[/tex]
Substitute y in any equation:
[tex]x = 2(y)[/tex]
[tex]x = 2(8) = 16[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.